Analysis Performance of Nursing Personnel in Inpatient Room "Darmayu" Hospital Ponorogo and the factors that Influence - Djemiran Djemiran (Journal for Quality in Public Health, 2020)
The hospital is a health organization that was formed because on the basis of community needs that are increasingly complex because people are starting to realize the importance of health. This requires a hospital to be able to provide a maximum service, especially to the community. The demand will get heavier if at the same time the globalization era emerges as it is today where the changes are increasingly faster and simultaneous if not balanced with professional and high quality Human Resources (HR). This is affecting the performance of officers in the hospital which includes: length of work, work status, commitment and loyalty as well as reward systems. The population in this study were 80 nurses in the inpatient room of the "Darmayu" General Hospital out of a total population of employees in the treatment room of 100 nurses. Data analysis techniques using multiple regression, while the program to conduct analysis tests using SPSS. There is a positive and significant effect between commitment and loyalty to the performance of nurses in the care room of the "Darmayu" General Hospital. There is a positive and significant influence between the reward system on the performance of nurses in the care room of the "Darmayu" General Hospital. There is a positive and significant influence between work status and the performance of nurses in the nursing room of the "Darmayu" General Hospital.